Perbandingan Induksi Misoprostol Dengan Induksi Oksitosin Terhadap Lama Persalinan Pada Kehamilan Postterm di RSU PKU Muhammadiyah Delanggu Klaten. - Dianggra, Phitra Sekar (Jurnal Kedokteran Indonesia, 2009)
Background: The incidence of postterm pregnancy accounts 10% of all pregnancies, and causes perinatalmortality 3 to 5 time as many as full-term pregnancy, depending on placenta function. Labor inductioncan lessen perinatal mortality if it is carried out before the emergence of insufficency signs. Oxytocinhas often been used for labor induction, but recently misoprostol has been increasingly used. Thisstudy aimed to compare the effect of misoprostol induction and oxytocin induction on labor time inpostterm pregnancy.Methods: This study was a double-blinded randomized controlled trial (RCT). The target populationwas mothers with postterm pregnancy who undertook induction. The source population was motherswith postterm pregnancy who undertook induction and gave birth at RSU PKU MuhammadiyahDelanggu, Klaten, Central Java. Eighteen postterm mothers undertook oxytocin induction and 18postterm mothers undertook misoprostol induction. Confounding factors that were controlled forincluded maternal age, parity, gestation age, birth weight, Apgar score, and Bishop score. The datawas analyzed by independent t test, by use of SPSS version 16.Results: This study showed that misoprostol induction shortened on average 3.5 hours less thanoxytocin, and this difference was statistically significant (p<0.001). This result was consistent withanother related finding that showed higher Bishop score in misoprostol induction than oxytocininduction.Conclusion: It is concluded that labor time induced by misoprostol is shorter than oxytocin in posttermpregnancy. Misoprostol can be used to replace oxytocin as a faster inductor for postterm pregnancy.Keywords : postterm pregnancy, oxytocin induction, misoprostol induction, labor time